2013
DOI: 10.19026/rjaset.5.4743
|View full text |Cite
|
Sign up to set email alerts
|

Application and Comparison of Altman and Ohlson Models to Predict Bankruptcy of Companies

Abstract: Environment fluctuation and increasing competitiveness between corporations lead to make the achievement of proper benefit more difficult. Therefore, financial decision making received more attention compare to past few decades and it forces managers to apply novel techniques and methods in order to make excellent decisions. This study tries to investigate the application of Altman and Ohlson models as two of these techniques. To achieve this goal companies from Tehran Stock Exchange are chosen because there a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 12 publications
1
19
0
3
Order By: Relevance
“…Whenever financial ratios are utilized to analyze a company, it is important to note that no economic analysis technique is perfect (Gerantonis et al, 2009, Summers and Sweeney, 1998, Karamzadeh, 2013. For instance, the Z-Score is merely reliant on the underlying financial data reported by the company.…”
Section: Resultsmentioning
confidence: 99%
“…Whenever financial ratios are utilized to analyze a company, it is important to note that no economic analysis technique is perfect (Gerantonis et al, 2009, Summers and Sweeney, 1998, Karamzadeh, 2013. For instance, the Z-Score is merely reliant on the underlying financial data reported by the company.…”
Section: Resultsmentioning
confidence: 99%
“…To categorize the models it was evaluated that all the companies become successful in estimation. Karamzadeh (2013) Vol.11, No.19, 2019 7 companies listed at BEI and concluded that Grover model gives highest accuracy in predicting bankruptcy followed by Springate, Zmijewski and Altman models. Grice and Dugan (2003) examined Ohlson and Zmijewski models.…”
Section: Empirical Studies5mentioning
confidence: 99%
“…Assessing the probability of failure by using 171 Journal of Technology Management for Growing Economies, Volume 8, Number 2, October 2017 Karamzadeh (2013) compared the predictive accuracy of Altman's model and Ohlson's model and it was observed that Altman model is a better predictor of bankruptcy and outperformed the Ohlson's model because correct classification rate of Altman model was found to be higher than Ohlson's model. Alareeni and Branson (2013) tested the Altman's Z-score model for manufacturing and non-manufacturing companies.…”
Section: Reveiw Of Literaturementioning
confidence: 99%
“…After the development of the Altman's model many authors or researchers developed their own models by using different variables and methodology. Many studies like Agarwal and Taffler (2005), Sarbapriya (2011), Rayalaseema and Muhammad (2012), Anjum (2012), Karamzadeh (2013), Altman et al (2014), Celli (2015) etc. tested the predictive accuracy of the Altman's model by applying it to the recent time period and it was found that Altman's model is still a powerful tool to predict the bankruptcy.…”
Section: Introductionmentioning
confidence: 99%